2023
DOI: 10.1088/1741-4326/ace3d9
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent collisional radiative modeling of tungsten in the magnetic sheath for erosion diagnosis

Abstract: Tungsten is the material of choice for the divertors in ITER, SPARC and future fusion reactors. Accurate diagnosis of tungsten erosion and migration is important for first wall life time, slag production and core performance. The addition of a magnetic presheath requires time-dependent collisional radiative effects to be included for accurate neutral tungsten collisional radiative modeling. Gross erosion measurements could be modified by a factor of 10 due to the inclusion of time-dependent effects for ITER re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Using excitation rates from a new non-perturbative Dirac R-matrix electron-impact calculation for WI [36], it can be shown that the total value of the ionization coefficient for neutral tungsten is relatively insensitive to changes in the metastable fraction, whereas photo-emission coefficients strongly depend on the distribution of the electron population among metastable states [37]. Consequently, populations of the various metastable levels of tungsten atoms can be important in determining an appropriate S/XB coefficient for those plasma conditions [38]. Using the Python solver ColRadPy [39] to provide time-dependent solutions of a collisional-radiative model for tungsten neutral sputtered from divertor surfaces, it is shown that the evolution in time of the population of metastable levels of neutral tungsten can also impact the values of the S/XB coefficient [38] (figure 3(c)).…”
Section: Sheath Effects On Tungsten S/xb Coefficientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using excitation rates from a new non-perturbative Dirac R-matrix electron-impact calculation for WI [36], it can be shown that the total value of the ionization coefficient for neutral tungsten is relatively insensitive to changes in the metastable fraction, whereas photo-emission coefficients strongly depend on the distribution of the electron population among metastable states [37]. Consequently, populations of the various metastable levels of tungsten atoms can be important in determining an appropriate S/XB coefficient for those plasma conditions [38]. Using the Python solver ColRadPy [39] to provide time-dependent solutions of a collisional-radiative model for tungsten neutral sputtered from divertor surfaces, it is shown that the evolution in time of the population of metastable levels of neutral tungsten can also impact the values of the S/XB coefficient [38] (figure 3(c)).…”
Section: Sheath Effects On Tungsten S/xb Coefficientsmentioning
confidence: 99%
“…Consequently, populations of the various metastable levels of tungsten atoms can be important in determining an appropriate S/XB coefficient for those plasma conditions [38]. Using the Python solver ColRadPy [39] to provide time-dependent solutions of a collisional-radiative model for tungsten neutral sputtered from divertor surfaces, it is shown that the evolution in time of the population of metastable levels of neutral tungsten can also impact the values of the S/XB coefficient [38] (figure 3(c)). Furthermore, as spectral lines are each dominantly driven by a single metastable state, population of metastable states can be experimentally inferred from the measurements of spectral line ratios [37].…”
Section: Sheath Effects On Tungsten S/xb Coefficientsmentioning
confidence: 99%